TANGGUNG JAWAB INDONESIA TERHADAP PENCARI SUAKA INTERNASIONAL BERDASARKAN PRINSIP KEMANUSIAAN (STUDI KASUS PENCARI SUAKA INTERNASIONAL DI KALIDERES JAKARTA BARAT) - Muhammad Gani Lukita; Ida Kurnia (Fakultas Hukum Universitas Tarumanagara, 2020)
The problem of asylum seekers and refugees is a matter of human rights (HAM), as well as a problem in international law. In 1951 the United Nations created The Convention Relating Status of Refugees 1951 (Convention Concerning the Status of Refugees 1951). Therefore, the Perpers regarding the Handling of Refugees from Abroad No. 125 of 2016. Even though this Perpres has been issued, it is still unable to complete the handling of asylum seekers and refugees in Indonesia, especially international asylum seekers in Kalideres, West Jakarta, where the asylum seekers are Not getting enough attention from the government. The formulation of the problem in writing this journal is How the responsibility of the Indonesian government in handling asylum seekers in Kalideres is seen from humanitarian principles. In this paper, the method used is a normative research method in which the author approaches legal principles. In this study the authors use legal sources, namely: the 1945 Constitution of the Republic of Indonesia, the Law of the Republic of Indonesia Number 37 of 1999 concerning Foreign Relations, Law of the Republic of Indonesia Number 6 of 2011 concerning Immigration and Perpers regarding the Handling of Refugees from Outside. Negeri No. 125/2016, as well as The Convention Relating Status of Refugees 1951. From those problems, the authors conclude that the handling of asylum seekers and refugees is an obligation for the Indonesian government, because human rights are an obligation mandated by the 1945 Constitution of the Republic of Indonesia and international law.